The Deixin in Class VII Indonesian Language at SMP Negeri 7 Seluma For The 2023 Academic Year. - Fanhari, Muhammad Fauzan; Rahayu, Ngudining; Wardhana, Dian Eka Candra (Jurnal Korpus, 2025)
The focus of this research is the application of deixis by teachers and students of class VII SMP Negeri 7 Seluma in interactions learning Indonesian. The research method used is a descriptive method with data collection techniques namely observation techniques, note-taking techniques and recording techniques. The collected data is processed using 5 steps, namely 1) Data transcription; 2) Data identification; 3) Data classification; 4) Data interpretation; and 5) Conclusion. The results of the research found 3 types of deixis, namely personal deixis which is divided into three parts, including: singular first person deixis with the characteristic "I, I" and plural first person deixis with the characteristic "we, us", second singular person deixis with the characteristic " you, you, you" and plural second person deixis with the characteristics "you (all), you (all), you", third person singular deixis with the characteristics "he, he, her" and plural third person deixis with the characteristics "they" ; spatial deixis such as “here, there, to here, to there, from here, from there”; and time deixis such as "tomorrow, the day after tomorrow, later, later, earlier, yesterday, last week".